(3HQfGeL CfTWI aj afhf GdCOGA dJfejI HYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(2-4) (3SfhGJ (B= s Activities Program for performance arts to develop some development's needs to nursery child (2-4) years old - (3OjfG LeGd SdjeGf YLjR s; (3SYGO GdSjO EHQGgje (B: s; (3YHjQ HcQj aQGL(B: s; (3ceGd GdOjf MSjf (B: s ((3GdbGgQI (B: s (3OjfG LeGd SdjeGf YLjR (B: s, 2017)
(3jgOa GdHMK Edi(B/ (3GdJMbb ef aGYdjI HQfGeL CfTWI aj afhf GdCOGA dJfejI HYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(2-4) (3SfhGJ haj cd eQMdI YeQjI ef (B(2-3): (3-4) (3SfhGJ(B: (3hbO Je GSJNOGe GdefgL THg GdJLQjHj(B: (3hJchfJ YjfI GdHMK ef(B: (60) (3WadkG hWadI aj GdeQMdI GdYeQjI ef(B(2-4) (3SfhGJ(B: (3efge (B(30) (3WadkG hWadI aj GdeQMdI GdYeQjI ef (B(2-3) (3SfhGJ ebSejf Edj (B(15) (3eLehYI JLQjHjI(B: (15) (3eLehYI VGHWI(B: (30) (3WadkG hWadI aj GdeQMdI GdYeQjI ef (B(3-4) (3SfhGJ ebSejf Edj (B(15): (3eLehYI JLQjHjI (B(15) (3eLehYI VGHWI(B: (3CeG COhGJ GdHMK(B: (3abO bGeJ GdHGMKI HGSJNOGe GSJeGQI edGMXI GdSdhcjGJ GdeQJHWI HHYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(2-3) (3SfhGJ ef hLgI fXQ (B((3eYdeI GdMVGfI(B): (3hef hLgI fXQ(B((3GdhGdOjf(B) ((3EYOGO(B/(3GdHGMKI(B): (3GSJeGQI edGMXI GdSdhcjGJ GdeQJHWI HHYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(3-4) (3SfhGJ ef hLgI fXQ (B((3eYdeI GdMVGfI(B): (3hef hLgI fXQ(B((3GdhGdOjf(B) ((3EYOGO(B/ (3GdHGMKI(B): (3ebjGS COGFj ddSdhcjGJ GdeQJHWI HHYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(2-3) (3SfhGJ (B((3EYOGO(B/ (3GdHGMKI(B): (3ebjGS COGFj ddSdhcjGJ GdeQJHWI HHYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(3-4) (3SfhGJ (B((3EYOGO(B/ (3GdHGMKI(B): (3HQfGeL CfTWI aj afhf GdCOGA dJfejI HYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(2-3) (3SfhGJ(B((3EYOGO(B/ (3GdHGMKI(B): (3HQfGeL CfTWI aj afhf GdCOGA dJfejI HYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(3-4) (3SfhGJ (B((3EYOGO(B/(3GdHGMKI(B): (3hCSaQJ GdfJGFL Yf(B: (3JMbb aGYdjI HQfGeL CfTWI aj afhf GdCOGA dJfejI HYV GdGMJjGLGJ GdfeGFjI dWad GdMVGfI ef (B(2-4) (3SfhGJ aj cd eQMdI YeQjI ef (B(2-3): (3-4) (3SfhGJ(B: (3hGSJeQGQjI CKQ GdHQfGeL hCfTWJg Ydj cd ef GdeQMdJjf aj GdbjGS GdJJHYj s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQjHI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdCSGSjI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGMJjGLGJ GdfeGFjIs; (3Wad GdMVGfg ef (B2-4 (3SfhGJ s; (3afhf GdGOGAs